REDESIGN JARINGAN HOTSPOT UNTUK INDOOR COVERAGE DI GEDUNG AGROKOMPLEK LANTAI 4 UNIVERSITAS UDAYANA - Bimantara Putra, Bayu; Putra Sastra, Nyoman; Wiharta, Dewa Made (Jurnal SPEKTRUM; Vol 7 No 1 (2020): Jurnal SPEKTRUM, 2020)
Hotspots are signaled areas that refer to certain places (usually public places) and have internet services using wireless local area network (WLAN) technology. Because the installation of the device and the user who is accessing it is indoors, of course it will be faced with a barrier / barrier in the form of a wall that prevents the entry of the radio signal so that the hotspot signal coverage is unable to cover optimally. This condition occurs in the WLAN network of Agrokomplek Building, Udayana University. So it is necessary to measure the coverage area of the hotspot signal so that no blank spots occur. The results of the measurement of the 4th floor coverage of the Udayana University Agrokomplek Building showed that the signal coverage experienced a lot of attenuation caused by distance and barriers in the form of walls. To increase the signal level value, an access point is added in an area that does not get signal coverage.